Software development as a methodological strategy in Civil Engineering - Quiñones-Cuenca, Santiago; García-Ramírez, Yasmany (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The software is necessary to improve the designs and operation of civil engineering projects. Despite its valuable contribution, during the Civil Engineer's training, it is more important to know the physical and mathematical elements behind each model. A combination of both, as software development, could enhance their learning. Therefore, this study aims to propose a learning methodology based on software development for Civil Engineering students. The methodology was applied to the iRAP model to evaluate road safety.